Study on the pathogenesis of MiR-6324 regulating diarrheal irritable bowel syndrome and bioinformatics analysis - Xiao, Jin; Zhou, Yan-ni; Yang, Yan-lin; He, Li; Wang, Ke-kai; Chen, Min (Frontiers in Pharmacology, 2023)
Objective To investigate the pathogenesis of IBS-D by bioinformatics analysis of the differential microRNAs in rat colon tissue and to analyze and predict the function of their target genes. Methods Twenty male Wistar rats of SPF class were randomly divided into two groups, the model group was manipulated using the colorectal dilatation method + chronic restraint stress method to establish the IBS-D model; while the blank group stroked the perineum at the same frequency. Screening of differential miRNAs after High-throughput sequencing of rat colon tissue. GO and KEGG analysis of target genes using the DAVID website, further mapping using RStudio software; the STRING database and the Cytoscape software were used to obtain the protein interaction network (PPI) of the target genes as well as the core genes. Finally, qPCR was used to detect the expression of target genes in the colon tissue of two groups of rats. Results After the screening, miR-6324 was obtained as the key of this study. The GO analysis of target genes of miR-6324 is mainly involved in protein phosphorylation, positive regulation of cell proliferation, and intracellular signal transduction; it affects a variety of cellular components such as cytoplasm, nucleus, and organelles on the intracellular surface; it is also involved in molecular functions such as protein binding, ATP binding, and DNA binding. KEGG analysis showed that the intersecting target genes were mainly enriched in cancer pathways, proteoglycans in cancer, neurotrophic signaling pathway, etc. The PPI network screened out the core genes mainly Ube2k, Rnf41, Cblb, Nek2, Nde1, Cep131, Tgfb2, Qsox1, and Tmsb4x. The qPCR results showed that the expression of miR-6324 decreased in the model group, but the decrease was not significant. Conclusion miR-6324 may be involved in the pathogenesis of IBS-D as a potential biological target and provide further ideas for research on the pathogenesis of the disease or treatment options.